If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -12 = 12 + -2p Reorder the terms: -12 + 2y = 12 + -2p Solving -12 + 2y = 12 + -2p Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2y = 12 + 12 + -2p Combine like terms: -12 + 12 = 0 0 + 2y = 12 + 12 + -2p 2y = 12 + 12 + -2p Combine like terms: 12 + 12 = 24 2y = 24 + -2p Divide each side by '2'. y = 12 + -1p Simplifying y = 12 + -1p
| 2u=12 | | 2x^4+16x^3+32x^3=0 | | x^2-8x-14=0 | | x^3+8x+14=0 | | (w+3)7=-7 | | 0=x^2-14x+49 | | 13=m | | 3(x-2)=12x | | 9y-8-5y=5y-5 | | [3t-2]+6=2 | | -9+5x+2=48 | | 1.5t=-9 | | 8=12y+6x | | .6w=.48 | | 4(m+6)=4 | | 3x-12+3=33 | | 63=9m | | 2h+4h-9h=h | | a-11=-18 | | 10x-4x-2-1=15 | | 4[1-(-6x-2)]=120x+44 | | 4[1-(6x-2)]=120x+44 | | 5x-(2x-1)=10+2(3-x) | | 3x^2-5=34 | | -.4=g-4.9 | | -5x-6+9x=34 | | 2x^2+3+5x=0 | | 5(b-6)=90 | | -5(x+9)-7=-52 | | 4x^2+5y^2-20=0 | | 6(3y-7)=56 | | 176576=2x+29888 |